Russian-Ukraine 2022 War: A Review of The Economic Impact of The Russian-Ukraine Crisis on The Several Developing Countries - Pavel, Alexei Svetlana; Oksana, Dmytro Anastasiya (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The war between Russia and Ukraine is one of the international tragedies that burden many countries today—affected countries incident war, Of course in Europe. Supply energy in Europe is almost half more originates from Russia, so war makes the area of Europe and around No stable. Another problem is war. It also involves many countries, not only Russia and Ukraine, directly. War Russia opposes Ukraine has caused enhanced consumption of energy and food on the ground in Europe. The rupture crisis economy causes enough inflation high in several countries. Therefore appearance challenges the economy in modern times. Peace and stability in the world economy should be maintained, now ravaged by war. War raises Lots of dire consequences for the world community. Among other things, the raw material price rose sharply and changed the global energy trading system. Plus, with the increased price of energy and items, attacks Russia to Ukraine, the supplier country food. As a result, food shortages threaten and influence hunger in the global community. Wartime has influenced many countries, such as increasing food and fertilizer prices. In condition this kind is necessary, there is an action real from the United Nations to complete the organization's most extensive international at this time. Due to the war between Russia and Ukraine in 2022, a crisis economy happened, plus there is Covid 19. Several impacts price of commodity oil and gas rebound high, a threat to food, and stock market shocks.